2009
DOI: 10.1093/jpepsy/jsp112
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hippocampal Activity in Youth with Posttraumatic Stress Symptoms: An fMRI Study

Abstract: Decreased activity of the hippocampus during a verbal memory task may be a neurofunctional marker of PTSS in youth with history of interpersonal trauma. The results of this study may facilitate the development of focused treatments and may be of utility when assessing treatment outcome for PTSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
98
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 56 publications
3
98
0
7
Order By: Relevance
“…Human brain imaging studies subsequently showed that I‐ELT was associated with altered structural integrity in the limbic system (Aas et al., 2012; Andersen et al., 2008; Bremner et al., 1997; Carrion, Weems, & Reiss, 2007; Corbo et al., 2014; Dannlowski et al., 2012; Driessen et al., 2004; Lupien et al., 2011; Tottenham et al., 2010; Veer et al., 2015). Functional imaging studies have further shown that, when processing emotional stimuli (e.g., angry faces), I‐ELT was associated with increased activity in the amygdala (Bremner et al., 2005; Grant, Cannistraci, Hollon, Gore, & Shelton, 2011; Maheu et al., 2010), and with decreased activity of the hippocampus (Bremner et al., 1999; Bremner et al., 2003; Carrion, Haas, Garrett, Song, & Reiss, 2010) and anterior cingulate cortex (Bremner, Vythilingam, Vermetten, Southwick, McGlashan, Nazeer, et al., 2003; Bremner, et al., 2003; Bremner et al., 2004; Mueller et al., 2010). However, these studies have been limited by the consistent use of emotional stimuli, preventing assessments of whether I‐ELT‐related limbic dysfunction potentially impacts more general aspects of cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Human brain imaging studies subsequently showed that I‐ELT was associated with altered structural integrity in the limbic system (Aas et al., 2012; Andersen et al., 2008; Bremner et al., 1997; Carrion, Weems, & Reiss, 2007; Corbo et al., 2014; Dannlowski et al., 2012; Driessen et al., 2004; Lupien et al., 2011; Tottenham et al., 2010; Veer et al., 2015). Functional imaging studies have further shown that, when processing emotional stimuli (e.g., angry faces), I‐ELT was associated with increased activity in the amygdala (Bremner et al., 2005; Grant, Cannistraci, Hollon, Gore, & Shelton, 2011; Maheu et al., 2010), and with decreased activity of the hippocampus (Bremner et al., 1999; Bremner et al., 2003; Carrion, Haas, Garrett, Song, & Reiss, 2010) and anterior cingulate cortex (Bremner, Vythilingam, Vermetten, Southwick, McGlashan, Nazeer, et al., 2003; Bremner, et al., 2003; Bremner et al., 2004; Mueller et al., 2010). However, these studies have been limited by the consistent use of emotional stimuli, preventing assessments of whether I‐ELT‐related limbic dysfunction potentially impacts more general aspects of cognition.…”
Section: Introductionmentioning
confidence: 99%
“…These findings contrast with those of a second recent study that solely examined the encoding period and identified hippocampal irregularities during an associative memory task in a small group of patients. 3 Broadly surveying functional imaging studies in the psychiatric literature, only recently has hippocampal function been examined using functional magnetic resonance imaging (fMRI) in patients with disorders such as posttraumatic stress disorder (PTSD) [4][5][6] or anxiety. 7 Even in patients with schizophrenia, in whom there are clear disruptions of functional networks involving the temporal lobes, hippocampal function has been explored in only a handful of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Maltreated children show increased amygdala and hippocampus activation in response to threatening faces (15)(16)(17)(18), reduced hippocampus activation in a declarative memory task (19), and variable findings regarding PFC activation (12). These brain areas do not act in isolation but interact to regulate the fear response.…”
mentioning
confidence: 99%